Berkeley Model 5602-20 Nuclear Scaler (1950)
General view of an unidentified woman, presumably a model, holding up component parts of a nuclear scaler produced by the Berkeley Division of Beckman Instruments. A scaler is an electronic instrument used to count radiation-induced pulses from radiation detectors such as a Geiger-Muller tube.
Keywords: Scientific apparatus and instruments; Beckman Instruments, Inc.; Nuclear energy